Molecular tuning for electrochemical CO₂ reduction - Zhang, Jincheng (2023)
Electrochemical carbon dioxide reduction reaction (CO2RR) offers unprecedented opportunities to alleviate the greenhouse effect and produce valuable chemicals/fuels simultaneously. Recently, molecular tuning has emerged as a powerful method to modify catalyst's surface and has been verified effective in improving CO2RR performance. However, a comprehensive and insightful review of this topic is still missing. Herein, we first summarize the reaction pathways of CO2RR to produce C1 and C2 products, followed by discussion of the merits of molecular decoration. Next, density functional theory (DFT) calculation toward different products is elaborated. Relative experiments using various molecular tuning strategies are then demonstrated, including regulating electronic structure of catalysts, stabilizing important intermediates, creating confinement effect, protecting active sites, and serving as active sites or linkers to promote tandem catalysis. The relationship between molecular structure and CO2RR performance is thoroughly recapped. Finally, several issues regarding the future development of molecular tuning are raised, and the corresponding solutions are provided.